Interpretation of Moral and Religious Value in Emha Ainun Najib's Poems - Bety Wahyuni; Supriyono Supriyono; Joko Sutrisno AB; Tommy Hastomo (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2020)
The problem studied in this thesis is the interpretation of the moral and religious values in the poems of Emha Ainun Najib. Interpretation is carried out on these poems which show moral and religious values. This study uses a qualitative method with a content analysis approach. The data of this research are the six poems by Emha Ainun Nadjib and in terms of the content of the moral and religious values conveyed by the authors. The results showed that the collection of Emha Ainun Nadjib's poems conveyed both moral and religious values. Moral messages and religious messages conveyed in general provide teachings about monotheism to readers about the importance of surrendering only to Allah SWT, the importance of maintaining aurat for women, the importance of protecting oneself from usury which is forbidden by religion, and the importance of being a devout human being but still in a religious position. There are 10 poems that have been interpreted, the dominant one conveyed by Emha Ainun Nadjib is a religious value. Moral values are conveyed in poetry but only in a few lines in poetry. The moral and religious values conveyed can at least provide life lessons for readers to draw closer to God and be humble in the midst of religious life and society.